Perancangan Evaluasi Vendor pada Departemen Ekspor-Impor di PT X - Tirza Christina Seputra; Herry Christian Palit (Jurnal Titra, 2020)
Vendor evaluation is an important activity to assess vendor performance. PT X is a manufacturing company that manufactures bicycle. Vendor evaluation on export-import department in PT X has been done periodically, every six month. However, the evaluation has been done subjectively because the assessment is qualitative. It is also didn’t give the final conclusion whether the vendor’s performance was good or bad. This is because there are no indicators that indicate whether the vendor’s performance was good or bad. This study applies analytical hierarchy process method in redesigning vendor evaluation to help the company in making multi-criteria decisions. Evaluation items are redefined through the interview and given weights that represent the company’s preferences in evaluating vendors. Evaluation items and weights are arranged into vendor evaluation forms using Microsoft Excel. The results of the study are 3 types of vendor evaluation designs, namely for export vendor EMKL, import vendor shipping agent, and import vendor EMKL.